Identification and functional characterisation of glycoside hydrolases from the kauri dieback pathogen, Phytophthora agathidicida : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Plant Science at Massey University, Manawatū, New Zealand - Bradley, Ellie Lynn (Massey University, 2022)
The survival of kauri, an ancient conifer species endemic to New Zealand, is currently threatened by kauri dieback disease, caused by the oomycete plant pathogen Phytophthora agathidicida. As P. agathidicida continues to spread throughout kauri forests in the northern North Island of New Zealand, encouraging research has indicated there may be natural tolerance to the disease within the kauri population. This resistance is likely governed, in part, by the plant immune system, which is activated upon recognition of pathogen invasion patterns such as microbe-associated molecular patterns (MAMPs), damage-associated molecular patterns (DAMPs), and effectors (virulence factors required for host colonisation), which are recognised at the plant cell surface by plant immune receptors. To better understand how P. agathidicida interacts with its plant host on a molecular level, pathogenproduced proteinaceous invasion patterns need to be identified and characterized to aid in the identification of cognate immune receptors in the plant host, which may be involved in activation of the plant immune system. As the role of glycoside hydrolase (GH) proteins in virulence and pathogenicity of fungal and oomycete plant pathogens is well established (Chapter two), an effectoromics approach was used to identify six P. agathidicida GH12 proteins that appear to act as MAMPs in both Nicotiana benthamiana and Nicotiana tabacum (Chapter three). Furthermore, nuclear magnetic resonance was used to identify considerable changes in kauri leaf apoplastic wash fluid of approximately 17 metabolites, including sucrose and glucose, in response to P. agathidicida inoculation (Chapter four), thus suggesting a role for GH proteins in the hydrolysis of some of these metabolites. Finally, proteomic analysis of P. agathidicida culture filtrates via liquid chromatography-mass spectrometry (LC–MS) was used to validate the expression of predicted P. agathidicida proteins and to investigate the capacity of this method to identify candidate invasion patterns for future analysis. Chapter five established that LC–MS analysis of Phytophthora culture filtrate was an effective method for the identification of putative apoplastic invasion pattern candidates and confirmed the production of all six P. agathidicida GH12 cell death elicitors in culture. Collectively, this thesis has advanced our understanding of the molecular mechanisms underpinning the interaction of P. agathidicida with its host and has contributed to the identification of candidate apoplastic effectors.
Figures are re-used with permission.
Listed in 2023 Dean's List of Exceptional Theses
Keywords: Kauri; Diseases and pests; Dieback; Phytophthora diseases; New Zealand; Glycosidases; Dean's List of Exceptional Theses; 310805 Plant pathology